Heat and Mass Transfer of a Peristaltic Electro-osmotic Flow of a Couple Stress Fluid through an Inclined Asymmetric Channel with Effects of Thermal Radiation and Chemical Reaction - Reddy, Kattamreddy Venugopal; Reddy, Machireddy Gnaneswara; Makinde, Oluwole Daniel (Periodica polytechnica. Mechanical engineering - Mas̆inostroenie, 2021)
The presented article addresses the electro-osmotic peristaltic flow of a couple stress fluid bounded in an inclined asymmetric micro-channel. The viscous dissipation, Joule heating and chemical reaction effects are employed simultaneously in the flow analysis. Heat and mass transfer have been studied under large wavelength and small Reynolds number. The resulting nonlinear systems are solved numerically. The influence of various dominant physical parameters is discussed for velocity, temperature distribution, concentration distribution and the pumping characteristics. Electro kinetic flow of fluids by micro-pumping through micro channels and micro peristaltic transport has accelerated considerable concern in accelerated medical technology and several areas of biomedical engineering. Deeper clarification of the fluid dynamics of such flow requires the continuous need for more delicate mathematical models and numerical simulations, in parallel with laboratory investigations.